2001
DOI: 10.1128/iai.69.7.4407-4416.2001
|View full text |Cite
|
Sign up to set email alerts
|

Deletion ofwboAEnhances Activation of the Lectin Pathway of Complement inBrucella abortusandBrucella melitensis

Abstract: Brucella spp. are gram-negative intracellular pathogens that survive and multiply within phagocytic cells of their hosts. Smooth organisms present O polysaccharides (OPS) on their surface. These OPS help the bacteria avoid the bactericidal action of serum. The wboA gene, coding for the enzyme glycosyltransferase, is essential for the synthesis of O chain in Brucella. In this study, the sensitivity to serum of smooth, virulent Brucella melitensis 16M and B. abortus 2308, rough wboA mutants VTRM1, RA1, and WRR51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 62 publications
2
50
0
Order By: Relevance
“…Regarding the interaction of Brucella with human complement, it has been demonstrated that the bacteria are considerably more resistant to the killing action of human serum than other Gram-negative bacteria (5,39). In spite of this, the binding of human complement components to the surface of B. abortus was conspicuous and commensurate with the opsonization of this bacterium by normal serum.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the interaction of Brucella with human complement, it has been demonstrated that the bacteria are considerably more resistant to the killing action of human serum than other Gram-negative bacteria (5,39). In spite of this, the binding of human complement components to the surface of B. abortus was conspicuous and commensurate with the opsonization of this bacterium by normal serum.…”
Section: Discussionmentioning
confidence: 99%
“…Because CA180 killed macrophages rapidly, we have also postulated that the rough mutants are killed when exposed to complement and other bactericidal factors after the infected macrophages lyse. However, reports of resistance of B. melitensis rough mutants to complement-mediated lysis (16) suggests a different possible fate for such organisms. The fact that rough organisms are rarely identified in clinical specimens suggests that spontaneously occurring rough derivatives may be similar to B. abortus RB51 or B. canis, but characterization of such mutants does not support this contention.…”
Section: Discussionmentioning
confidence: 99%
“…This attenuation has been ascribed to the increase in both the antibodyindependent complement activation [3,27,44] and the sensitivity to polycationic bactericidal peptides [3,47,74,105]. In addition, R mutants display altered attachment to cells [32,48,115].…”
Section: Brucella Rough (R) Mutantsmentioning
confidence: 99%